Level of discomfort (Journal of Parents and Teachers, 2013)
Almost everything that surround us, from the workplace to the relations that we build and maintain or even the activities we carry out, have a great impact in the educational efficiency. However, despite the corrosive nature of this situation, nobody seems to be paying attention leading to a situation in which emotional base, essential foundation of humans to achieve good results while working with satisfaction and efficiency, is being undermining. Because of that, it is completely necessary to check regularly the emotional state and the degree of anxiety and well-being/discomfort that we experience, so that it is possible to apply protective, corrective and prophylactic measures.
Keywords: Classroom management; Socio-emotional education; Discomfort; Teacher body; education.